1998
DOI: 10.1029/97ja03144
|View full text |Cite
|
Sign up to set email alerts
|

The transport of plasma sheet material from the distant tail to geosynchronous orbit

Abstract: Abstract. Several aspects of mass transport in the Earth's plasma sheet are examined. The evolution of plasma sheet material as it moves earthward is examined by statistically comparing plasma sheet properties at three different downtail distances: nearEarth plasma sheet properties obtained from measurements by 1989-046 near the geomagnetic equator near midnight at 6.6 RE, midtail plasma sheet properties obtained from ISEE 2 measurements during 333 encounters with the neutral sheet, and distant-plasma sheet pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
166
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(177 citation statements)
references
References 135 publications
11
166
0
Order By: Relevance
“…However, as we have mentioned above a few complications, such as the overall lack of latitudinal coherence of the observed PsA patches, hint that the role of ULF waves in regulating the PsA structures was only partial; some other magnetospheric processes that affect the occurrence of the PsAs, particularly in the radial direction, might be at play as well. For example, the earthward flows are known as being capable of transporting plasma "bubble/blob" structures into the near-Earth CPS, which are then subject to the turbulent mixing and/or cascading to smaller spatial scales [Borovsky et al, 1998;Borovsky and Funsten, 2003;Vörös et al, 2006]. This process might structure the CPS noncoherently and in turn contribute to the irregularly spatial occurrence of the PsAs.…”
Section: Discussionmentioning
confidence: 99%
“…However, as we have mentioned above a few complications, such as the overall lack of latitudinal coherence of the observed PsA patches, hint that the role of ULF waves in regulating the PsA structures was only partial; some other magnetospheric processes that affect the occurrence of the PsAs, particularly in the radial direction, might be at play as well. For example, the earthward flows are known as being capable of transporting plasma "bubble/blob" structures into the near-Earth CPS, which are then subject to the turbulent mixing and/or cascading to smaller spatial scales [Borovsky et al, 1998;Borovsky and Funsten, 2003;Vörös et al, 2006]. This process might structure the CPS noncoherently and in turn contribute to the irregularly spatial occurrence of the PsAs.…”
Section: Discussionmentioning
confidence: 99%
“…Combined with a reasonably low value of the magnetic field (B∼5-10 nT), this leads to minimum (for the entire magnetosphere) representative values of the Alfvén velocity A=B/ 4πm p n ∼10 2 km/s. It is not inconceivable that the values A∼(30-50) km/s exist (Borovsky et al, 1998). The boundary of the plasma sheet presented in Fig.…”
Section: The Resonator In the Near-earth Part Of The Plasma Sheetmentioning
confidence: 99%
“…It has been suggested in particular that the density of the plasma sheet having access to the inner magnetosphere through geosynchronous orbit may have an impact on the ensuing magnetospheric activity (e.g., Borovsky et al, 1998;Kozyra et al, 1998;Thomsen et al, 1998). The studies by Thomsen et al (2003) and Lavraud et al (2005) showed that the observation of cold and dense plasma at geosynchronous orbit is likely due to the inward transport of the cold, dense plasma sheet (CDPS) that is occasionally observed in the tail of the magnetosphere (c.f.…”
Section: B Lavraud Et Al: Observation Of Two Distinct Cold Dense Imentioning
confidence: 99%